Experience with Atorvastatin in Conservative Management of Chronic Subdural Hematoma with Brief Review of Literature - Roka, Yam Bahadur; Karki, Mohan; Dahal Chettri, Arati (Nepal Journal of Neuroscience, 2022)
Chronic subdural hematoma (CSDH) is one of the most common neurosurgical procedure done in any neurosurgical unit worldwide. The majority of CSDH are operated upon and there are very few studies regarding its conservative management. Mannitol, Steroids, Tranexemic acid, middle meningeal artery embolization and Angiotensin Converting Enzyme inhibitors are some options to treat CSDH conservatively. Atorvastatin is one of the newer and novel drugs that has been used effectively to medically treat CSDH. This is a retrospective study of 20 cases of CSDH that were managed conservatively with atorvastatin between 2015 to 2021. A total of 20 (7.5%) cases were included in the study period (January 2015 – January 2021). Glasgow Coma Score (GCS)/ Markwalder score (MS), mode of injury if any, age, sex, symptoms and neurological findings, co-morbidities, anti-platelet use, radiological finding of midline shift at admission and outcome with Glasgow outcome score (GOS) at the end of two months after treatment recorded. Atorvastatin in dose of 20 mg daily was given for maximum of two months with repeat CT/MRI scans done at 2 months. Repeat scan was done at 2 weeks and at 2 months and all of them showed complete resolution of the CSDH radiologically. The Glasgow outcome score showed good improvement in all the cases although there was mild confusion in five of the elderly which can be attributed to age related behavior changes. We conclude that atorvastatin can be used safely in not only elderly but also in younger subjects.